Fatigue Failure Model for Polymeric Compliant Systems. (31st March 2013) - Akano, Theddeus T.; Fakinlede, Omotayo A.
Abstract : Fatigue analysis and lifetime evaluation are very important in the design of compliant mechanisms to ensure their safety and reliability. Earlier models for the fatigue prediction of compliant mechanisms are centred on repeated and reversed stress cycles. Compliant mechanisms (CMs) are now being applied to situations where the fatigue is caused by random varying stress cycles. It is, therefore, necessary to consider fatigue resulting from random varying stress cycles and damage caused to the compliant material. A continuum damage mechanics (CDM) model is proposed to assess the fatigue life of polymeric compliant mechanisms. The elastic strain energy is computed on the basis of a nearly incompressive hyperelastic constitution. The damage evolution equation is used to develop a mathematical formula that describes the fatigue life as a function of the nominal strain amplitude under cyclic loading. Low density polypropylene (LDP) is used for the fatigue tests conducted under displacement controlled condition with a sine waveform of 10 Hz. The results from the theoretical formula are compared with those from the experiment and fatigue software. The result from the prediction formula shows a strong agreement with the experimental and simulation results.